Implementation of Academic Services in Increasing Student Satisfaction of the Faculty of Administrative Sciences at the Universitas Pembinaan Masyarakat Indonesia Medan - Cut Sah Kha Mei Zsazsa; Boby Indra Prayoga (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to determine how the implementation of academic services in increasing student satisfaction at the Faculty of Administrative Sciences, Universitas Pembinaan Masyarakat Indonesia Medan. This study uses a qualitative descriptive approach. Research informants consist of several informants, namely the Academic Bureau and special students of the Faculty of Administrative Sciences. The data collection techniques use literature studies, direct observation and in-depth interviews. Based on the results of the study, it shows that the implementation of academic services in increasing student satisfaction at the Faculty of Administrative Sciences at Universitas Pembinaan Masyarakat Indonesia Medan is optimal. Based on the results of the study seen from the research indicators, namely showing indicators of service quality, namely direct evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance) and (empathy) have been implemented well. And indicators for measuring student satisfaction, namely service procedures, service requirements, ability/competence, fairness in getting service, certainty of service schedules, environmental comfort, and service security have also been implemented well.